A salmonella-challenge impacts the variability of performance, body composition and lysine requirements of growing pigs under poor housing conditions - Ortiz, M. T. [UNESP]; Arnaut, P. R. [UNESP]; Valini, G. A.C. [UNESP]; França, I. [UNESP]; Silva, C. A. [UNESP]; de Oliveira, M. J.K. [UNESP]; Marçal, D. A. [UNESP]; Melo, A. D.B. [UNESP]; Hauschild, L. [UNESP] (Elsevier, 2024)
Reduced performance for pigs under challenging sanitary conditions is a well-documented response, but little is known about its effect on the variability in performance and nutrient requirements. This study aimed to evaluate the impact of a sanitary challenge in the variability of growth performance, body composition and lysine (Lys) requirements of growing pigs. Data of 40 animals from a population of 120 growing female pigs (25.4 ± 3.7 kg) that were either raised in good sanitary condition (SC) (n = 20) or inoculated with 5 mL of 2 × 109 UFC of S. Typhimurium (ST) and raised under poor SC (ST + Poor; n = 20) in a 28-day trial. For this study, only the pigs fed the control diet and which had body composition measured were used. Observed individual daily feed intake (DFI) and BW data were smoothed by linear regression. Protein deposition (PD) was estimated considering predicted daily gain (DG) and the relation between observed PD and DG. These variables were integrated in a factorial equation to estimate daily individual Lys requirements. During the first experimental week, animals in the ST + Poor SC had higher rectal temperature, higher haptoglobin and lower albumin concentrations than the animals in the Good SC (P < 0.05). The sanitary challenge also caused reductions (P < 0.05) in final BW (- 9.5 %), ADG (-20.3 %), DFI (-8.5 %), and PD (-20.3 %). For ST + Poor SC pigs, Lys requirements were 19.4 % lower on day 28 and 9.9 % lower throughout the experimental phase compared to Good SC pigs. When analysing individual pig variability, compared to GOOD SC, pigs under ST + Poor SC had a greater CV for final BW (+19.2 %), ADG (+41.5 %), DFI (+22.5 %), PD (+41.5 %), and for Lys requirements (+29.0 %) throughout the experimental phase. Moreover, the differences in Lys requirements between the least and the most demanding pigs were 17 % in the ST + Poor SC, and 14 % in the Good SC. These results demonstrate that despite the sanitary challenge reducing BW, ADG, DFI, PD, and Lys requirements, it enhances the variability of growth performance, body composition and Lys requirements of growing pigs.
Keywords: Factorial method; Protein deposition; Salmonella Typhimurium; Sanitary conditions